Hematological and muscle damage values in amateur players during football season (Annals of Medical Research, 2021)
Aim: Acute intensive physical exercise induce the hematological changes in circulation. However, the effect of football training on hematological and biochemical parameters during the football season is still limited. The present study aimed to investigate the effects of routine football training on physiological parametrs namely: hematological, biochemical and iron levels during the pre and competitive match season. Materials and Methods: Amateur football players (n=15) participated in this study. The blood samples were collected and physical performance parameters assesses twice during pre and end of the first league between August and December. The players also performed Cooper run test, 30 m sprint tests. In addition, the hematological and biochemical parameters were analyzed by taking blood samples during pre and end of the first league. Results: Football training resulted in significant decreased erythrocyte (RBC) concentration (p0.001), hemoglobin level (Hb) (p0.01), mean corpuscular hemoglobin concentration (MCHC) (p0.01), lymphocyte (Lymph), (p0.05) unlike the level of neutrophil (Neut), (p0.001), mean corpuscular volume (MCV) (p0.05), mean platelet volume MPV (p0.001) values were increased at the end of the league. The biochemistry parameters of the lactate dehydrogenase (LDH) (p0.001) and urea (p0.01) concentrations were increased whearas the level of alanine aminotransferase (ALT), (p0.05) was decreased at end of the season. The creatine kinase (CK) and paraoxonase (PON1) activity was unaltered during the football training season. The level of the unsaturated iron binding capacity (UIBC) increased (p0.05) and iron (Fe) level decreased end of the season (p0.05). Moreover, football training had no effect on physical performance tests results (p>0.05). Conclusion: Football season mostly had effects on hematological and iron parameters with LDH, urea; this may be related the football training intensity.
Keywords: Amateur players; damage parameters; football training; football season